The Effect of Role Conflict and Work Stress on Employee Performance with Organizational Citizenship Behavior as a Moderating Variable in Bank Indonesiarepresentative Office of North Sumatera Province - Ita Pebriquartina Sirait; Mesra B (Equivalent : Journal of Economic, Accounting and Management, 2026)
This study aims to examine the influence of role conflict and work stress on employee performance, with Organizational Citizenship Behavior (OCB) as a moderating variable at the Bank Indonesia Representative Office in North Sumatra Province. This study used a quantitative approach through Structural Equation Modeling (SEM) analysis using SmartPLS 3.0 software. The study sample included all employees working at the Bank Indonesia Representative Office in North Sumatra Province. The results showed that role conflict and work stress had a negative and significant influence on employee performance, while OCB had a positive and significant influence. The moderating effect of OCB on the relationship between role conflict and work stress on employee performance was also proven significant, with the first moderation strengthening the relationship, while the second moderation weakening the effect of the independent variable on performance. This study provides theoretical contributions regarding the importance of OCB as a moderating variable, as well as practical implications for management in controlling role conflict, managing work stress, and enhancing OCB behavior to encourage improved employee performance.